Homophobia and Sport Experience: A Survey of College Students - Anderson, Mark B.; Butki, Brian D.; Heyman, Steven R. (My University, 1997)
Athlete (n = 246) and nonathlete (n = 135) students (381 total) from a mid-sized, rural university completed the Attitudes Towards lesbians and Gay Men Scale (ATLG; Herek, 1984). Average ratings for attitudes toward and perceptions of gay men and lesbians ranged from negative to mixed. Females scored significantly lower on homophobia than males, while athletes rated sigriificantly higher on homophobia than nonathletes. The results suggest that athletes, at least those from primarily rural areas, have less tolerance for lesbians and gay men than nonathletes. Results and implications for counselors are discussed in the context of the conservatism of athletics, sport as an arena of masculinity, heterosexism, lack of knowledge about lesbians and gay men, and other sociocultural influences.
Keywords: homophobia; rural; sex/gender; demographics